Students' Entrepreneurial Interest As A Mediation Of The Influence Of Entrepreneurship Education, Digital Literacy And Social Media On Student Entrepreneur Success At Feb State University Of Yogyakarta - Fidya Pramesti; Sukirno Sukirno (FKIP, Universitas Palangka Raya, 2025)
This study aims to analyze students' entrepreneurial interest as a mediation of the influence of entrepreneurship education, digital literacy and social media on the success of student entrepreneurs at FEB UNY. This study is a comparative causal research with a quantitative approach. The subjects of the study were PE FEB UNY students. The population was 175 and the sample was 122. The sampling technique was probability sampling. Data analysis used path analysis. Results of the study; There is a positive and significant influence of entrepreneurship education, digital literacy, social media on students' entrepreneurial interest. There is a negative and significant influence of entrepreneurship education, digital literacy, social media on the success of student entrepreneurs. There is a positive and significant influence of students' entrepreneurial interest on the success of student entrepreneurs. There is a significant influence of entrepreneurship education, digital literacy, social media on the success of student entrepreneurs through the mediation of students' entrepreneurial interest. The success of student entrepreneurs does not only depend on the resources they have, but how these resources are managed and utilized, especially through high entrepreneurial interest. Entrepreneurship education provides knowledge and skills, while digital literacy and social media provide tools to access information and reach markets. Entrepreneurial interest serves as a link that optimizes the use of these resources, enabling students to be more proactive and innovative in running their businesses